1983
DOI: 10.2307/3281046
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Requirements of Schistosoma japonicum Eggs

Abstract: Newly laid eggs of Schistosoma japonicum were cultured in a serum-free, chemically defined medium, RPMI 1640, which contained 20 amino acids, glutathione, 11 vitamins, and glucose in a balanced salt solution. The requirements for these components in the nutrition of the eggs was investigated by the deletion of single component from the medium. The following 14 amino acids were shown to be essential for the full development of the egg in the medium: L-arginine, L-cystine, glycine, L-histidine, L-isoleucine, L-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
1

Year Published

1986
1986
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 14 publications
1
8
0
1
Order By: Relevance
“…The longevity of the parasites in vitro in this study had the objective to their survival for long periods out of In the present study, egg hatching was observed in RPMI 1640 and RPMI 1640 + agar 2% treatments and the parasites did not show any body alterations until day 18 of exposure at 24 °C. The same was observed after 19 days at 28 °C as was reported in a study by Kawanaka et al (1983) for the culture of S. japonicum for 48 h in RPMI 1640 medium supplemented with 10% fetal calf serum. The authors concluded that 14 amino acids present in the medium (L-arginine, L-cysteine, glycine, L-histidine, L-isoleucine, L-leucine, L-lysine, L-methionine, L-phenylalanine, L-serine, L-threonine, L-tryptophan, L-tyrosine, and L-valine) and choline chloride were essential for the development of S. japonicum eggs.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The longevity of the parasites in vitro in this study had the objective to their survival for long periods out of In the present study, egg hatching was observed in RPMI 1640 and RPMI 1640 + agar 2% treatments and the parasites did not show any body alterations until day 18 of exposure at 24 °C. The same was observed after 19 days at 28 °C as was reported in a study by Kawanaka et al (1983) for the culture of S. japonicum for 48 h in RPMI 1640 medium supplemented with 10% fetal calf serum. The authors concluded that 14 amino acids present in the medium (L-arginine, L-cysteine, glycine, L-histidine, L-isoleucine, L-leucine, L-lysine, L-methionine, L-phenylalanine, L-serine, L-threonine, L-tryptophan, L-tyrosine, and L-valine) and choline chloride were essential for the development of S. japonicum eggs.…”
Section: Discussionsupporting
confidence: 85%
“…Conversely, Roswell Park Memorial Institute (RPMI) 1640 culture medium that was developed for human leukemic culture in suspension is considered adequate for use in a wide variety of mammal cells including HeLa, Jurkat, MCF-7, PC12, PBMC, astrocytes, and carcinomas, and has been widely applied in parasite culture. Kawanaka et al (1983) observed egg hatching of Schistosoma japonicum (Katsurada, 1904) cultured in RPMI 1640 medium supplemented with 10% fetal calf serum. For fish parasites, Brázová et al (2012) observed 3 weeks survival of the acanthocephalan Acanthocephalus lucii (Müller, 1776) and the cestode Proteocephalus (Weinland, 1858), which are both parasites of Perca fluviatilis in RPMI 1640 culture medium.…”
Section: Introductionmentioning
confidence: 96%
“…The production of vitelline cell metabolites is required mainly for shell formation, with very little being used for embryo nutrition; the uptake and utilisation of a range of exogenous metabolites from the host tissue by the shelled embryos of schistosomes has been demonstrated both in vivo and in vitro (Kawanaka et al 1983;Sternholm and Warren 1974). As suggested by Tinsley (1983), the key to the developmental and invasive strategies of schistosomes lies in extending the exploitation of host resources during embryonic development, such that, in the apparently unique case of schistosomes, the egg itself is parasitic.…”
Section: Discussionmentioning
confidence: 99%
“…However, schistosome eggs are known to take up and metabolize exogenously supplied nutrients (1)(2)(3)(4) Recently it was demonstrated that newly laid eggs of S. japonicum can be cultured in serum-free RPMI 1640 (9). Kawanaka et al (10) have further defined and simplified the composition of the minimum essential nutrient medium supporting the development of newly laid eggs of S. japonicum.…”
Section: Introductionmentioning
confidence: 99%